Model Terapi Kolase Berbasis Nilai Pesantren untuk Meningkatkan Adaptasi Sosial Santri Baru - Agus Sulthoni Imami; Uswatun Hazanah (Lembaga Yasin AlSys, 2026)
Problems of social adaptation frequently experienced by new santri in the pesantren environment, particularly during the transition period when they encounter a religious culture, strict discipline, and distinctive collective values—can potentially trigger anxiety, social withdrawal, and even maladaptive behavior. This study aimed to develop and analyze a collage therapy model grounded in pesantren values as a strategy to enhance the social adaptation skills of new santri at Pondok Pesantren Zainul Anwar Alasumur Kulon, Kraksaan, Probolinggo. A descriptive qualitative method was employed, with data collected through observation, in-depth interviews, and documentation involving new santri, mentor teachers, and the pesantren caregivers. The findings show that the collage therapy model integrated with pesantren values such as ukhuwah (brotherhood), independence, sincerity, and discipline helps santri to recognize their emotions, express personal experiences, and understand as well as internalize the social values that govern life in the pesantren. The participants exhibited positive changes, including increased self-disclosure, improved ability to work collaboratively, greater self-confidence, and more adaptive attitudes toward pesantren rules and daily dynamics. The study concludes that collage therapy based on pesantren values is effective as a creative, reflective, and educative approach to strengthening the social adaptation of new santri. Its implications suggest that this therapeutic model can serve as an alternative intervention within orientation and coaching programs for new santri and can be replicated in other pesantren-based educational institutions as a preventive strategy to minimize social adaptation barriers.